Frequency of UCP2 45-bp Ins/Del polymorphism in Saudi population from Jazan area and its association with autoimmune hypothyroidism UCP2 45-bp Ins/Del frequency in hypothyroidism - Kaabi, Yahia A.; Mansor, Abdullah S.; Alfagih, Ashwag S.; Hakami, Alhussain M.; Summ, Mohammed A.; Mjery , Yahia A.; Alzughbi, Mona N.; Habibullah, Mahmoud M. (International Journal of Health Sciences, 2020)
Objectives: Autoimmune hypothyroidism (AHT) is a common endocrine disorder. Although the exact cause of AHT is not yet understood, genetic factors may play a major role. Uncoupling protein 2 (UCP2) is a member of mitochondrial protein family involved in the regulation of cellular metabolism. An important functional polymorphism in the UCP2 gene, 45-bp insertion/deletion (ins/del) polymorphism, has been linked to certain clinical conditions. However, an association between the 45-bp ins/del polymorphism and AHT has not yet been established. Methods: In this study, about 259 blood samples were collected from, patients with AHT and age-matched healthy control subjects. DNA was extracted for UCP2 45-bp ins/del polymorphisms genotyping, using a standard polymerase chain reaction technique. The distribution of different genotypes was determined in both groups and possible association with AHT was also assessed by logistic regression analysis using the Del/Del variant as a reference genotype. Results: The frequency of the UCP2 45-bp ins/del polymorphism in the total study population was 49.04%, 40.15%, and 10.81% for Del/Del, Ins/Del, and Ins/Ins genotypes, respectively. The logistic regression analysis showed crude odds ratios (ORs), respectively, with their 95% confidence intervals (CIs) and P-values in codominant (Del/Ins) (OR = 1.53, CI = 0.89–2.60, P = 0.17), codominant (Ins/Ins) (OR = 0.75, CI = 0.34–1.74, P = 0.53), dominant (OR = 1.30, CI = 0.79–2.16, P = 0.37), and recessive (OR = 0.62, CI = 0.29–1.36, P = 0.30) inheritance models tested, where none of which were statistically significant. Conclusion: Our data revealed the distribution of the UCP2 45-bp ins/del polymorphisms in Jazan area and confirmed the lack of association between these genetic variants and the development of AHT.